Association of IL-6 Polymorphism -174G/C and Metabolic Syndrome in Hypertensive Patients. (28th February 2015) - Teixeira, Andrei Alkmim; Quinto, Beata Marie Redublo; Dalboni, Maria Aparecida; Rodrigues, Cassio Jose de Oliveira; Batista, Marcelo Costa
Abstract : Introduction . Visceral obesity, the central core of metabolic syndrome (MetS), is conceived as the pathogenic basis of an increased cardiovascular burden and is related with changes in cytokines. We investigated whether IL-6-174G/C gene polymorphism is associated with MetS prevalence in hypertensive patients. Method . A population of hypertensive patients was included and stratified by the presence of MetS according to IDF criteria and evaluated by Framingham risk score. The IL-6-174G/C genotyping was performed by polymerase chain reaction and the prevalence of MetS was compared between "C" carrier and "non-C" carrier groups. Results . From an original sample of 664 patients, 612 (34.2% men, age 57.3 ± 10.1, 30.4% diabetics) were included. MetS was diagnosed in 51.3% of total population and "C" carriers demonstrated high prevalence of MetS (P < 0.05 ) and each of its components. On binary logistic regression, it was observed that the IL-6 polymorphism was independently associated with occurrence of MetS, even after adjusting for covariates (OR 1.13–2.37, 95% CI, P < 0.05 ). Conclusion . The C allele at the -174 locus of IL-6 gene is independently associated with the occurrence of metabolic syndrome, emphasizing the importance of inflammatory genetic background in the pathogenesis of visceral obesity and related cardiovascular burden.